Rancang Bangun Rekonstruksi 3D Dengan Kinect Xbox 360 - Ningtias, Trisni Wahyu; Joni, Koko; Alfita, Riza (Universitas Muhammadiyah Jember, 2020)
Technology development is increasing rapidly and effectively brings an impact on the field of technology. One of them is scanning objects using a computer. Object scanning is a technology that combines hardware to see objects and software to process data that has been received by the hardware. The traditional manufacturing process without 3D scanning involves the design, analysis and testing of prototypes needs a very long time and expensive. Whereas 3D scanning is considered capable of being more efficient and practical. This research is conducted to facilitate the 3D scanning process by utilizing sensors on the Kinect 360 camera. The object will be scanned with a 360 camera to get data on each side. The results obtained will be processed by the system and process it into 3D objects. The process of collecting object data using Eclipse software while object rotation using a stepper motor which controlled by arduino. Based on the results of tests from research, the infrared sensor on the Kinect camera is less than optimal in reflecting light back on the object that has uneven surfaces. But the sensor works well on the object that has a flat surface.